2013
DOI: 10.1002/jocb.31
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Self‐Perceptions and Job Requirements on Creative Problem Solving

Abstract: Over the years, researchers have focused on ways to facilitate creativity in the workplace by looking at individual factors and organizational factors that affect employee creativity (Woodman, Sawyer, & Griffin, ). In many cases, the factors that affect creativity are examined independently. In other words, it is uncommon for researchers to look at the interaction among individual and organizational factors. In this study, it is argued that to get a true understanding of how to maximize creativity in the workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In research on innovation, it may be beneficial to explore the interaction of individual and environmental factors (Robinson-Morral, Reiter-Palmon, & Kaufman, 2013). In this study, we linked job satisfaction to creative self-efficacy and employee innovation.…”
Section: Discussionmentioning
confidence: 99%
“…In research on innovation, it may be beneficial to explore the interaction of individual and environmental factors (Robinson-Morral, Reiter-Palmon, & Kaufman, 2013). In this study, we linked job satisfaction to creative self-efficacy and employee innovation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prior studies have suggested the importance of individual differences in shaping the relationship between a contextual factor and employee innovation (e.g. Choi, ; Oldham & Cummings, ; Rank, Nelson, Allen, & Xu, ; Robinson‐Morral et al, ; Wu et al, ). In particular, in their reviews, Hennessey and Amabile (Hennessey, ; Hennessey & Amabile, ) suggest that individual differences such as one's initial level of intrinsic interest in a task may be an important factor in this regard.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…While some individuals enjoy coming up with new ideas and implementing them, others lack such an interest. Drawing insights from recent studies (e.g., Malik, Butt, & Choi, ; Robinson‐Morral, Reiter‐Palmon, & Kaufman, ; Wu, Parker, & de Jong, ), in this study, we build on and extend the sensemaking perspective by underscoring the importance of examining individual differences when understanding the effects of external influences on employee innovative behavior. Specifically, we propose that perceived innovation job requirement would have a stronger positive effect on innovative behavior for employees with lower levels of intrinsic interest in innovation.…”
mentioning
confidence: 98%
“…This creative problem solving approach extends to more real settings, where either the task is composed of real elements (for instance: "Design a device that allows people to pick up a book from a shelf (e.g. in a library) that is out of their reach, for instance, above their head") (Cardoso & Badke-Schaub, 2011), or the participants are real employees given a real problem related to their work environment (Robinson-Morral, Reiter-Palmon, & Kaufman, 2013). Third, beyond the sole individual level, many qualitative case studies have focused on methods, tools and techniques deployed in teams, firms and organizations to support different facets of creativity.…”
Section: Methodological Approaches To Creativitymentioning
confidence: 99%